Determinants of Employees’ Occupational Well-being during the COVID-19 Pandemic - Juchnowicz, Marta; Kinowska, Hanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The aim of this paper is to explore the determinants of occupational well-being in employees under the conditions of the COVID-19 pandemic. Research Design & Methods: The paper presents the results of a survey, conducted in January 2021, using the CAWI method, on a representative sample of working Poles (N=1,000). Hierarchical cluster analysis, Ward’s method and one-way ANOVA test were applied in the analysis of the survey results. Findings: The empirical study identified three relatively homogeneous groups of employees depending on factors determining their occupational well-being. For the first group, interesting work and job security were the two most important factors, while work-life balance and good cooperation with the superior were the least important. The second group depends on one factor – job security – for its professional well-being, while it ascribes the least importance to job prestige and development opportunities. The third group also identifies only one factor - interesting work – as being the most important, and job security and job prestige as being the least important. Implications/Recommendations: As a result, two key factors were identified: job security and interesting work. Polish workers fall into three groups: 1) those for whom both of these factors are important, 2) those focused mainly on job security and 3) those who put interesting work above all else. Contribution: The article adds to the knowledge on the determinants of employees’ occupational well-being, particularly during the COVID-19 pandemic. The results are important for the conscious management of employees. They provide practical guidance to help motivate employees in the conditions that characterise work during a pandemic.